The Tasks of the Bid Opening and Bid Evaluation Committee in Accordance with Presidential Decree 15- 247 - Makrof, Mohamed (Journal of Legal Studies and Researches, 2022)
This study aims to clarify the role of the Bid Opening Committee and Evaluation of Bids in accordance with Presidential Decree No. 15-247, where the committee for the opening of envelopes and evaluation of the offers administrative and technical work presented to the contracting interest that gives the transaction or declare the futility of the procedure or cancellation of temporary grants for the transaction of other cases.